1997
DOI: 10.1108/02652329710194946
|View full text |Cite
|
Sign up to set email alerts
|

European corporate customers’ choice of domestic cash management banks

Abstract: Provides evidence of the criteria for the choice of domestic cash management banks adopted by large European firms. A questionnaire completed by 1,129 corporate customers from 20 European countries indicates that service quality is the most important criterion for choice of domestic cash management banking, followed by pricing and relationship. Using the empirical findings, discusses the appropriateness of relationshiporiented and transactionoriented bank strategies across Europe. Based on the customers' ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…This matching has led potential suppliers to seek brand differentiation through intangible associations (McDowell-Mudambi et al, 1997;Webster & Keller, 2004). Quality of service and relationship (Mols et al, 1997;Turnbull & Gibbs, 1989), along with trustworthiness (Zineldin, 1996) and helpfulness (Chan & Ma, 1990), are some of the most important attributes for financial service selection.…”
Section: Brand Knowledge Of Business Buyersmentioning
confidence: 98%
See 2 more Smart Citations
“…This matching has led potential suppliers to seek brand differentiation through intangible associations (McDowell-Mudambi et al, 1997;Webster & Keller, 2004). Quality of service and relationship (Mols et al, 1997;Turnbull & Gibbs, 1989), along with trustworthiness (Zineldin, 1996) and helpfulness (Chan & Ma, 1990), are some of the most important attributes for financial service selection.…”
Section: Brand Knowledge Of Business Buyersmentioning
confidence: 98%
“…In financial services, the product is described through an ability to obtain finance (Turnbull & Gibbs, 1989), a range that can satisfy needs (Chan & Ma, 1990), and technological capacity (Mols, Bukh, & Blenker, 1997;Zineldin, 1996). Price reflects the core (monetary) nature of the product (Mols et al, 1997;Zineldin, 1996). Supplier's fees, commissions, interest charged on loans, and interest paid on investments comprise this dimension (Chan & Ma, 1990).…”
Section: Brand Knowledge Of Business Buyersmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, pricing or service charges seemed to be a significant factor for lending between firms and banks, but this was not necessarily found in other bank products and services. Mols et al (1997) undertook an analysis of bank preferences by corporate customers across twenty European countries. They concluded that price and service quality were the most important bank selection criteria in general for European business firms.…”
Section: Business Firms' Attitudes Towards Islamic Financementioning
confidence: 99%
“…A number of justifications for this assumption can be advanced including the fact that nowadays many financial institutions engage in several types of banking, hence obscuring distinctions between various forms. Nearly all the banks make extensive use of direct mail, social media marketing and relationship marketing, resulting in public perceptions that banks offer the same products and, importantly, that they share common organisational traits (see Mols, Bukh, and Blenker 1997;Worcester 1997;Sandler 2002). This approach is compatible with the precepts of social identity theory (Tajfel and Turner 2003;Owens, Robinson, and SmithLovin 2010) which explains how a group of organisations can possess a collective identity defined in part by socio-political considerations, even though each member organisation has its own history and characteristics.…”
Section: Introductionmentioning
confidence: 99%